Digital games as sources for science analogies: Learning about energy through play. (March 2019) - Martin, Wendy; Silander, Megan; Rutter, Sarah
Abstract: Many research studies have focused on how game designs informed by learning theory can benefit students; fewer explore what needs to happen during instruction for students to translate what they learn in games into disciplinary knowledge. In this study, researchers examined whether instructional techniques that support visual mapping of analogies can help students translate game learning to science learning. The three digital games used in the study were designed to have images and actions that are analogous to photosynthesis, electricity, and heat transfer, topics that all relate to the larger crosscutting concept of energy transfer. We hypothesized that these digital games could serve as compelling, visual sources for analogies, but that teachers would need to explicitly map the relationships between the game visuals and the target science concepts for students to learn those concepts. Our study compared student learning outcomes from an intervention that combined digital gameplay with analogy mapping to outcomes from an intervention that used the same digital games without analogy mapping. We found that students who experienced analogy mapping learned more as measured by assessments of electricity and energy transfer. Findings from this study provide practical recommendations for integrating digital games into classroom instruction, as well as insights into how explicit analogical mapping supports sense-making and measurable progress toward accurate conceptual knowledge of complex scientific phenomena. Highlights: Our study looked at how students can learn science concepts from digital games. Teachers and students mapped analogies from digital games to target science concepts. Gameplay served as the analogy source. Students who used analogy mapping learned more about electricity and energy transfer.